Poverty impacts of food price increases in Ethiopia - Minot, Nicholas; Martin, Will (International Food Policy Research Institute, 2023)
After a long period of relatively stable prices on world markets, the prices of key food staples began to rise from around the beginning of 2020. This period of price increases, spanning the Covid-19 pandemic and then the price shocks following Russia’s invasion of Ukraine raised serious concerns about the welfare of poor people in countries such as Ethiopia.